Closing the Gap Between Emerging Initiatives and Integrated Strategies to Strengthen Science Diplomacy in Latin America - López-Vergès, Sandra; Macías-Navarro, Lorena; Hernández-Mondragón, Alma Cristal; Corrales-Aguilar, Eugenia; Soler, Marga Gual; Guerra, Melania (Frontiers in Research Metrics and Analytics, 2021)
Science diplomacy is a fast-growing field of research, policy and practice dedicated to understanding and reinforcing the connections between science and international affairs to tackle national, regional and global issues. By aligning science and diplomacy, countries can attract talent, strengthen their national research ecosystems, provide avenues for participation of scientists in policy and coordinate integrated solutions to challenges with technical dimensions. While Latin America has a long tradition of bilateral and regional cooperation, science still plays a marginal role in foreign policy, as has become evidenced by the response to the COVID-19 pandemic. With few exceptions, Latin American nations have a relatively immature science, technology and innovation ecosystem, compounded by low public and private investments in research, coexisting with profound socio-economic inequalities and large vulnerable populations. Such challenging conditions have created barriers to a fluid relationship between science and diplomacy, fundamentally characterized by inefficient communication between scientists and policymakers, weak collaboration channels and duplicated roles, which altogether perpetuate siloed mentalities and a lack of trust between the two communities. Over the last decade, a first influential wave of Latin American scientists, diplomats and other professionals, including five of the co-authors, have undertaken science diplomacy training provided by specialized organizations. Through these experiences, we recognized the need to elevate awareness and build capacities in science diplomacy in our respective countries and overall, across Latin America. Here we describe emerging efforts and mechanisms to bridge the gap between scientists and policymakers at the national and regional level. Furthermore, we offer recommendations to amplify the impact of those pioneering initiatives towards consolidating a robust science diplomacy practice across the region. The national experiences described from Costa Rica, Mexico and Panama can serve as a roadmap for other Latin American nations in the early process of developing a science diplomacy strategy, so they can also align themselves to a collective pathway. Most critically, we propose a way forward so that Latin America can leapfrog beyond disjointed training of individuals into integrated institutional strategies that can harness the tools of science diplomacy to enhance science-informed multilateral cooperation and enable more effective science-informed policymaking.